Morphological anisotropy of nano-dimensional arsenic trisulfide glass films and liquid crystal photoalignment. (13th April 2017) - Sharpnack, Lewis; Kirzhner, Miri G.; Agra-Kooijman, Deña M.; Chaudhary, Ashok; Kumar, T. Arun; Klebanov, M.; Sheremet, N.; Reznikov, Yu; Abdulhalim, I.; Kumar, Satyendra
ABSTRACT: The results of high-resolution x-ray reflectivity study of nano-dimensionally thin arsenic trisulfide (As2 S3 ) glass films reveal surface roughness anisotropy upon prolonged irradiation with polarized 436 nm blue light. The anisotropy correlates with the photoinduced anisotropy and LC photoalignment observed on these thin films. However, the As2 S3 film's thickness reduces drastically during the reflectivity experiments, and ambient oxygen and moisture penetrate the film and create a second altered thin layer on top of a thicker film of As2 S3 . The results confirm the viability of As2 S3 films for non-contact LC photoalignment material but suggests the need for further process optimization to reduce the films' degeneration to increase their effectiveness.